19. Forvikneset: Et aktivitetsområde fra eldre steinalder - Cerbing, Mikael; Kvalheim, Alice Sunde (Tromura, 2025)
Forvikneset was a largely disturbed Stone Age site dating to around 5100 BC. No features were recorded, but part of a cleared area was identified. Some production material, primarily rock crystal and quartz, was collected, but overall, there were few tool finds. It is possible that Forvikneset represents a specialized site focused on fishing in Tjeldsundet.
Keywords: Archaeological excavation; Late Mesolithic; Late Stone Age; Activity area